Experimental Study of Human Respiratory Detection Using UWB GPR - Buyukhan, Cansu; Orhan, Melek; Karamzadeh, Saeid; Caliskan, Alper; Cilesiz, Inci (IEEE, 2017)
Todays, Ground Penetrating Radar (GPR) System is used for civil applications such as detection of buried pipes, mine and military fields. One of the recent applications of GPR in civil and defense industry is detection of human vital signs through obstacles such as wall, rubble etc. In this study, we aim to set ultra-wideband ground penetrating radar system for detection human vital signs. For this purpose, system parameters will be designed and data acquisition will be performed successfully. For signal extraction of respiratory motion, Fast Fourier Transform will be applied on radar data.
Keywords: ground penetrating radar; ultrawideband; fourier transform; respiratory detection; Engineering